Teaching approaches to drugs in the context of the socio-educational system: an analysis about the lar do garoto - Almeida, Thaís Farias de (2023)
This article is an excerpt from the master's thesis defended in the Postgraduate Program in Education at the Federal University of Paraíba (UFPB), whose research was developed in the Socio-Educational Center Lar do Garoto, an educational establishment located in the municipality of Lagoa Seca, state of Paraíba, where adolescents who committed infractional acts are in execution of a socio-educational measure of internment. The study was approved by the Human Research Ethics Committee of the Medical Sciences Center of UFPB under opinion nº 5.255.702, on February 22, 2022. In the investigation, we aimed to analyze how the issue of drugs has been addressed in the school context of adolescents who are at Lar do Garoto. Methodologically, the research was operationalized through semi-structured interviews with teachers from the school operating in the socio-educational unit. The empirical material resulting from the interviews was scrutinized according to the procedures of the Thematic Analysis by Braun and Clarke (2006). Among the results, we observed different approaches of drugs, both guided by the prohibitionist logic of the “war on drugs”, and by approaches that reject it. Conclusively, it is emphasised the need to offer continuing formation to the socio-educational teachers about drugs, considering the challenges inherent to the theme and the context of adolescents assisted by the socio-educational system.